ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Achieving simultaneous wet adhesion, mechanical robustness, and long-term ionic conductivity in soft electronic interfaces remains a major challenge for the design of next-generation epidermal bioelectronics. Here, an injectable, muscle-conformal eutectogel comprising gelatin-based microgels and a polymerizable ternary eutectic solvent ([PTES]) is introduced, serving as a reactive medium and catalyst for rapid epoxy-amine crosslinking at physiological temperature. The [PTES] system establishes an extended hydrogen-bonding and ionic network that accelerates ring-opening reactions, enabling fast on-tissue gelation and robust adhesion. Compositional tuning reveals that increasing [PTES] content enhances complex viscosity by 114%, increases peel adhesion from 0.238 ± 0.063 to 0.309 ± 0.091·Nm -1 , and reduces swelling ratios from 432% to 332%, confirming the formation of denser dual dynamic-covalent networks. Electrical analyses show that polymerized [PTES] generates stable ionic pathways, decreasing initial resistance from 4.91±0.10 to 3.17±0.12 kΩ, with conductivity preserved over 5 days. The optimized eutectogel demonstrates excellent diabetic wound healing, high piezoresistive sensitivity with a gauge factor of 4.2 at 300% strain, enabling precise detection of both micro- and macro-scale human motions. Overall, this work establishes [PTES]-driven eutectogels as a versatile macromolecular platform that integrates injectability, wet adhesion, network toughness, and stable ionic conductivity for epidermal bioelectronics interfaces and soft mechanosensing applications.